1981
DOI: 10.2134/agronj1981.00021962007300050031x
|View full text |Cite
|
Sign up to set email alerts
|

Legume and Mineral N Effects on Crop Yields in Several Crop Sequences in the Upper Mississippi Valley1

Abstract: The total effect of legumes on subsequent crop yields may be divided into two categories: (i) the effect of the N that they supply, and (ii) the net effect of all other contributions. Knowing the size of these two effects, plus the N response of the subsequent crops, allows N fertilization to be optimized for decreased energy use and for reduced pollution potential. Because the size of the legume effects vary, a study was made to estimate them on a mesic, Typic Hapludalf soil at Lancaster, Wisconsin from 1967–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 11 publications
(19 reference statements)
3
76
1
2
Order By: Relevance
“…This synergistic relationship between 2 consecutive years of soybean (S-S-C-C) and N fertilizer for corn stover, ear and whole-plant DMY at Deschambault appeared to be due to rotation effects other than N-rotation effects, because no differences were.observed between corn from this crop sequence and monoculture at 0 kg N ha-r at both locations. In our study, rotation effects as defined by Baldock et al (1981) were not necessarily observed at the highest N level. Indeed, they defined the total rotation effect as the yield differential without N application, the rotation effects as the yield Can.…”
Section: Methodscontrasting
confidence: 53%
“…This synergistic relationship between 2 consecutive years of soybean (S-S-C-C) and N fertilizer for corn stover, ear and whole-plant DMY at Deschambault appeared to be due to rotation effects other than N-rotation effects, because no differences were.observed between corn from this crop sequence and monoculture at 0 kg N ha-r at both locations. In our study, rotation effects as defined by Baldock et al (1981) were not necessarily observed at the highest N level. Indeed, they defined the total rotation effect as the yield differential without N application, the rotation effects as the yield Can.…”
Section: Methodscontrasting
confidence: 53%
“…This is termed the "N benefit" of legumes. This suggests that the yield difference is due mainly to the improved soil N status following the legume (Baldock et al 1981). However, the yield gap often cannot be closed completely, indicating the involvement of some other factor(s) -the "non-N benefit" (Strong et al 1986;Wright 1990).…”
mentioning
confidence: 99%
“…Non-N or secondary benefits, i.e., rotational effects, are concluded when N response curves for the second-year cereal crop in cereal-cereal and pulse-cereal sequences do not converge, even at relatively high fertilizer N rates (Baldock et al 1981). Greater uptake of soil N by crops that succeed pulses may be attributed to: the effect of legumes in breaking cereal disease and pest cycles (McEwen et al 1989;Stevenson and van Kessel 1996a); higher residual soil water after pulse crops (Elliott et al 1987); enhanced nutrient cycling due to faster breakdown of legume crop residues in the soil to release nutrients other than N; better and deeper root growth as a result of improved soil properties (Toogood and Lynch 1959), such as soil tilth (Moldenhauer et al 1983); or reduction of phytotoxic and allelopathic problems associated with cereal crop residues and release of growth-promoting substances from decomposing legume residues (Ries et al 1977).…”
mentioning
confidence: 99%
“…Ci. Solo, 28:751-762, 2004et al (1981, as plantas de cobertura podem afetar uma série de atributos do solo, tais como: a umidade, a temperatura, a aeração e o controle de pragas e moléstias ("efeito rotação"), com reflexos positivos sobre o acúmulo de N das culturas em sucessão.…”
Section: Recuperação Pelo Milho Do N Adicionado Pelas Plantas De Cobeunclassified